Sports participation and muscle mass affect sex-related differences in bone mineral density between male and female adolescents: A longitudinal study - Luiz-de-Marco, Rafael [UNESP]; Kemper, Han; Agostinete, Ricardo Ribeiro [UNESP]; Werneck, André Oliveira [UNESP]; Maillane-Vanegas, Santiago [UNESP]; Faustino-da-Silva, Yuri da Silva [UNESP]; Exupério, Isabella [UNESP]; Fernandes, Rômulo Araújo [UNESP] (FapUNIFESP (SciELO), 2019)
BACKGROUND: Sports participation plays an important role in bone gain during childhood and adolescence. The aim here was to identify sex-related determinants of bone mineral density (BMD) differences between male and female adolescents, with emphasis on the role of sports participation. DESIGN AND SETTING: Longitudinal study conducted in a public university in Presidente Prudente, Brazil. METHODS: The sample comprised 48 adolescents aged 11-17 years, of both sexes, who were matched according to sex, age and sports participation. BMD was the main outcome, while muscle mass, sports participation, calendar age and biological maturation were treated as covariates. Participants were followed up after nine months. RESULTS: At baseline, BMD values were similar between the sexes. However, adjustment for covariates showed that BMD was higher among girls at all sites, with a contribution from lean soft tissue (LST) in the model (partial eta-squared, ES-r = 0.619 in upper limbs; 0.643 in lower limbs; 0.699 in spine and 0.599 in whole body). Sports participation only explained the upper-limb variance (ES-r = 0.99). At the follow-up, the results resembled the baseline except in the lower limbs (P = 0.109), in which BMD was similar between the groups. BMD gain over time was similar between girls and boys in all segments, and baseline LST affected upper-limb and whole-body BMD accrual (ES-r = 0.396 and 0.107, respectively). CONCLUSION: Whole-body and specific-site BMD differed between baseline and follow-up. However, BMD accrual was similar between the sexes, given that muscle mass constituted the most relevant determinant of the difference between them.
Keywords: Adolescent; Bone and Bones; Growth and Development; Puberty; Sports